Dynamics Analysis and Optimal Design of the Controllable Loading Mechanism - Zhang Lin; Li Junming; Wu Chengge; Cai Ganwei (Jixie chuandong)
The study object is the new controllable machinery loader,the design variable is the key parameters of boom lift branched,and the optimization goal is the least of maximum torque of the first during active-member lifting,and the constraints are overall layout,transmission angle and singularity,then the dimension optimization model of boom lift branched is built. What’s more,by using complex method,the numerical solving on optimization model is carried out and the best dimension parameters of each member of boom lift branched are obtained and the maximum drive torque of first active-member is lowered by 11%. Finally,the virtual prototype simulation based on ADAMS is conducted. The simulation result shows that the dynamics performance of optimized controllable loading mechanism is significantly improved. When boom is at the top position the first active-member is close to the inverse kinematics singular position and the power is reduced by80%. This study will provide a basis for performance promoting of controllable machinery loader.